THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON ELEMENTARY SCHOOL TEACHERS' PERFORMANCE - Muksalmina (el-Nizami : Jurnal Manajemen Pendidikan, 2024)
The purpose of this study was to analyze the influence of organizational culture and work motivation together on the performance of elementary school teachers in Kalidoni Subdistrict, Palembang City. This research uses quantitative methods. The population in this study was all educators in elementary schools in Kalidoni Subdistrict, Palembang City, with a total of 390 teachers. Based on the calculations that have been carried out, the sample size in this study was 79.6 or rounded to 80 people, around 41% of the total number of teachers in elementary schools in Kalidoni District, Palembang City. Data collection techniques use observation methods, questionnaires and documentation. Data analysis techniques use Coefficient of Determination Analysis, T Test (Partial), F Test (Simultaneous). The results of this study are (1) there is a positive and significant influence of organizational culture on teacher performance of 0.874. (2) there was a positive and significant influence of work motivation on teacher performance of 0.819. (3) there was a positive and significant influence of organizational culture and work motivation simultaneously on teacher performance by 0.908